Spatial-temporal patterns of euphausiids ecology in the Okhotsk Sea - Anatoly F. Volkov (Известия ТИНРО, 2015)
The most common regularities in spatial distribution of mass Euphausia species and their size classes and ontogenetic stages are determined for the Okhotsk Sea using the data averaging by biostatistical areas and applying the average results to the centers of the areas that allows to smooth small-scale patterns as patchiness. Thysanoessa raschii and Th. inermis occupy mostly shelf areas and Th. longipes and Euphausia pacifica - deep-water areas; among them Th. raschii and Th. longipes are more abundant and Th. inermis and E. pacifica are supposedly allochtonous species which penetrate to the Okhotsk Sea through the Kuril Straits, so they are distributed mainly in the southern part of the Sea. Mean biomass and abundance of all species in the upper (0-50 m) and deeper (50-200 m) layers are calculated for each stage and size class in the daytime and nighttime, separately: most of them, including both adults and furcilias, concentrate mainly in the deeper layer and their night biomass is higher in both layers though about a half of animals raise to the sea surface at night. Only eggs, nauplii and calyptopes of euphausiids don’t change their abundance considerably between day and night, and most of them occupy the upper layer round the clock. Obviously, the increasing of late furcilias and adults in the deeper layer at night is caused by their diurnal migration from the layers below 200 m. Seasons of the highest abundance for early stages come in natural order that is a sign of their short duration.